2020
DOI: 10.3390/app10051737
|View full text |Cite
|
Sign up to set email alerts
|

4-Hexylresorcinol Exhibits Different Characteristics to Estrogen

Abstract: 4-Hexylresorcinol (4HR) has been used as a food additive and antiseptic. The aim of this study was to evaluate whether the application of 4HR in breast cancer cells and ovariectomized rats showed estrogen-like effects. MCF-7 and SK-BR-3 cells were treated by solvent, 1–100 µM bisphenol-A (BPA), or 1–100 µM 4HR, respectively. 3-(4, 5-Dimethylthiazole-2-yl)- 2,5-diphenyltetrazolium bromide (MTT) assay and Western blot for extracellular signal-regulated kinase-1/-2 (ERK1/2), phosphorylated ERK1/2 (p-ERK1/2), estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The 4HR is used as a food additive because of its antibrowning effect [21], and it is suspected to be pseudo-estrogen [24]. However, 4HR administration in the ovariectomized rat model did not show an estrogenic effect [25]. In this study, the serum level of estrogen was not significantly different between the EF and CF groups (p > 0.05; Figure 3B), and 4HR showed HDACi activity in HUVECs [23].…”
Section: Discussionmentioning
confidence: 55%
“…The 4HR is used as a food additive because of its antibrowning effect [21], and it is suspected to be pseudo-estrogen [24]. However, 4HR administration in the ovariectomized rat model did not show an estrogenic effect [25]. In this study, the serum level of estrogen was not significantly different between the EF and CF groups (p > 0.05; Figure 3B), and 4HR showed HDACi activity in HUVECs [23].…”
Section: Discussionmentioning
confidence: 55%
“…According to a previous study [31], 4HR was suspected to be xenoestrogen. Although estrogen can increase angiogenesis [32], the effect and signaling pathway of 4HR are different from those of estrogen [33]. Accordingly, TGF-β1 is a key cytokine in skin wound healing, and 4HR increased its level of expression in this study.…”
Section: Discussionmentioning
confidence: 59%
“…1 ) and cDNA microarray assay (Table 2 ). Although this study focused on SCC-9 cells and OSCC, we also observed the inhibitory action of 4HR on breast carcinoma cell lines [ 18 ]. Besides, 4HR inhibited cell proliferation-related genes including cyclin C and other RNA polymerases by cDNA microarray assay (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for the potential use of 4HR as an anti-cancer drug, we have to mention the previous toxicology and carcinogenesis studies demonstrating that the oral administration of 4HR in doses up to 650–1000 mg/kg to animals unaffected their survival [ 9 ]. In the Zebra fish study, the administration of 4HR in doses up to 1 mM (194 μg/ml) is not teratogenic to the developing embryo [ 18 ]. The effective dose of 4HR, used for injections of carcinoma-grafted nude mice, was 10 mg/kg body weight, i.e., two orders of magnitude less, and caused no toxic side effects in our in vivo experiments [ 12 ].…”
Section: Discussionmentioning
confidence: 99%